NUCLEAR DESIGN CALCULATIONS OF THE NPP KRŠKO CORE - Kromar, Marjan; Trkov, Andrej (Journal of Energy Technology, 2024)
Nuclear design calculations of the NPP Krško core performed at the Jožef Stefan Institute are presented in this paper. The CORDͲ2 system, developed by the Reactor Physics Department, is intended for core design calculations of pressurized water reactors. It enables the determination of the core reactivity and power distribution. The software has been validated for the nuclear design calculations of PWR cores and has been used for the verification of the NPP Krško reload cores since 1990. The main components and the calculational methods of the CORDͲ2 system are briefly described in this paper.
Keywords: nuclear reactor; nuclear core design; nuclear calculation; PWR